Microbiological quality of typical foods served in Thai restaurants in Vienna, Austria - Awaiwanont N. (2014)
The microbiological quality, pH and serving size of typical meals served in 18 Thai restaurants in Vienna were studied. During the summer and winter season, one ready-to-eat food portion was sampled per restaurant and per food category ("A": raw or insufficient heat treatment; "B": heat treated main dish garnished/mixed with raw side-dishes; "C": thorough heat treatment, served alone; total number = 108). In addition, - where possible - some typical side dishes were sampled (n = 25). The average weight of main dishes varied dependent on category from 360-510 g.The lowest pH was observed in group "A" (average 4.5), most probably because of the addition of acids via lime juice. Expectedly, group "A" had significantly higher total aerobic counts (6.1 ± 0.8 log cfu/g) than group "B" (4 5 ± 1.7 log cfu/g) and "C" (2.6 ± 0 9 log cfu/g). In side-dishes, average total aerobic counts were higher in raw vegetables (4.9 log cfu/g) than in rice (2.6 log cfu/g). With respect to hygiene indicator bacteria, there was a clear association between presumably insufficient heat treatment and/or the likelihood of cross-contamination (groups X "B") on the one hand and the presence of E. coli and Enterobacteriaceae on the other. All 133 samples tested negative for Salmonella spp., Listeria monocytogenes and Campylobacter spp. (25 g aliquots). In groups "A" and "B" the warning limits for total aerobic count and Enterobacteriaceae established by the German Society for Microbiology and Hygiene were exceeded in 30-60 % of the samples. For food classification we used an empirical scheme taking into account heat treatment and the likelihood of cross-contamination, assuming that these two factors would be associated with the risk of presence of pathogenic bacteria in the ready- to-eat food portion. This empirical classification was well reflected in total aerobic counts. As regards pathogens, the usefulness of such a classification scheme could not be evaluated due to the low frequency of pathogens. This indicates that on this issue further studies should be conducted. © M. & H. Schaper GmbH and Co. ISSN 0003-925X.